Effect of seasonal variations and different housing systems on physiological responses and hematological parameters of buffaloes - KEKAN, P M; GARKAL, R A; KHARDE, S D; NARLADKAR, B W; MUNDE, V K (The Indian Journal of Animal Sciences, 2016)
An experiment was conducted to study the effect of 2 housing systems and seasonal variations on physiological responses and haematological parameters of buffaloes. Twelve buffaloes were selected and randomly divided into 2 equal groups. Animals of group A were housed in shade with net and animals of group B in shade without net. The experiment was conducted for 2 seasons i.e. monsoon and winter. The physiological responses were recorded weekly. Blood samples were aseptically collected fortnightly and were analyzed for hematological studies. All the parameters of physiological responses viz. respiration rate, rectal temperature, heart rate, and pulse rate were non significantly higher in group B as compared to group A in monsoon and winter seasons. Highly significant increase in mean values of Hb, TEC, TLC and PCV was observed in group A than the group B values in monsoon and winter seasons. Significantly higher values of lymphocytes and neutrophils was observed in group A during monsoon and non-significantly lower values in group B during winter season. Eosinophils and monocytes were non significantly higher in group B during monsoon and winter season as compared to group A. The temperature humidity index (THI) showed significantly lower in group A as compared to group B in both the seasons.